2014
DOI: 10.1260/1757-482x.6.3.179
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of the Primary Breakup Applying the Embedded DNS Approach to a Generic Prefilming Airblast Atomizer

Abstract: An improved understanding of the breakup processes of two-phase flows is essential to effectively control the fuel atomization for future aircraft engines. A detailed insight into the phenomena of primary breakup is a major limitation in gaining this knowledge. Aircraft engines use airblast atomizers to provide the fuel atomization. The geometries of airblast atomizers are complex, the operating conditions are characterized by high Reynolds-and Weber numbers. Direct Numerical Simulations (DNS) of liquid breaku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…Using the Smoothed Particle Hydrodynamics (SPH) method, characteristic breakup phenomena known from experimental findings of Gepperth et al [6] like liquid accumulation, ligament flapping and bag breakup are captured well numerically [8,9]. In simulations based on the Volume of Fluid method [10,11] and the Level Set method [12] the same good agreement with experimental observations is achieved. Precise numerical investigations enable a comprehensive understanding of primary atomization and serve as a basis for the development of new primary breakup models.…”
Section: Introductionmentioning
confidence: 71%
“…Using the Smoothed Particle Hydrodynamics (SPH) method, characteristic breakup phenomena known from experimental findings of Gepperth et al [6] like liquid accumulation, ligament flapping and bag breakup are captured well numerically [8,9]. In simulations based on the Volume of Fluid method [10,11] and the Level Set method [12] the same good agreement with experimental observations is achieved. Precise numerical investigations enable a comprehensive understanding of primary atomization and serve as a basis for the development of new primary breakup models.…”
Section: Introductionmentioning
confidence: 71%
“…Details on the fluid properties are summarized in Table 1, corresponding to a moderate Reynolds (Re = ρū g h c µ ≈ 13500) and Weber (W e l = ρū 2 g h l σ ≈ 8). This condition has been chosen since it has been extensively studied via experiments [9,10,12,21] and simulation through different methods [14,15,16,19,23]. Thus, a large amount of data is readily available for validation.…”
Section: Case Of Studymentioning
confidence: 99%
“…Given the simplicity of the planar configuration while still being representative of the breakup taking place in annular atomizers, most numerical studies have focused on the former geometry. DNS studies include Volume of Fluid (VOF) [14,15,16] frameworks; coupled VOF-Level Set [17,18,19]; or Smoothed Particle Hydrodynamics (SPH) in 2D [20,21] and 3D [22]. Studying the full atomizer geometry through DNS is unfeasible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harani and Sher [30] showed that the most uniform droplet distribution is obtained when angle of impact between the air jet and the liquid jet is 30°. Recently, the design and optimization of airblast atomizer geometry highly relies upon high-accuracy numerical simulations to shorten the research time and to reduce research expenses [31,32]. Additionally, physical properties of fuels also greatly affect the size of spray droplets in fuel spray.…”
Section: Chapter 1 General Introductionmentioning
confidence: 99%